Bargaining and the Joint-Cost Theory of Strikes: An Experimental Study - Sopher, Barry (Journal of Labor Economics, 1990)
This article reports on an experiment that was designed to test predictions about the frequency of disagreement (strikes) in games with complete information. An empirical test of the "joint-cost" theory, which relates strike activity to the marginal cost of striking, is based on a set of "shrinking pie" games in which subjects bargained in consecutive periods over how to divide a sum of money. Strike activity was a frequent occurrence in these games and, moreover, did not disappear over time. The joint-cost theory received some support, indicating that further tests may be useful.